Andayani & Sarido, L. (2013). Uji empat jenis pupuk kandang terhadap pertumbuhan dan hasil tanaman cabai keriting (Capsicum annum L.) Jurnal Agrifor, 12(1), 22-29. Badan Pusat Statistik. 2022. Statistik Tanaman Sayuran dan Buah Buahan Semusim Indonesia 2022. Diakses dari https://www.bps.go.id/publication/2018/10/05/bbd90b867a6ee3727f51c4 3/statistik-tanaman-sayuran-dan-buah---buahan-semusim indonesia-2022 .html pada tanggal 20 Januari 2020. Junus, M. H., Budya, S dan A.Syamsul. 2007. Pengaruh Li - ng, emo emo (Jurnal Agroterpadu, 2024)
This research was carried out in Tumpiling village, Wonomulyo subdistrict, Polewali Mandar district, West Sulawesi province, taking place from March 2023 to June 2023, with the aim of determining the effect of providing cow dung biogas waste and immersion time on the growth and production of large chili plants (Capsicum annum l). This research method was carried out in the form of a randomized block design (RAK) with a factorial pattern consisting of 2 factors. The first factor is the application of cow dung biogas waste fertilizer which is symbolized by (B) which consists of 3 levels, namely: B1, B2, B3, B4 and the second factor is the time for pruning shoots (perempelan) (P) consisting of three levels, namely: P0 ,P1,P2. The results of the observations showed that the provision of 40 tons/ha of cow dung biogas waste and pruning of the generative period (B4P2) had a good effect on increasing the production of chili plants.